A profanação da biopolítica em o caderno rosa de Lori Lamby, de Hilda Hilst - Werres, Débora França Teixeira (2023)
This master's research had as its main thematic focus the critical and reflective study of the biopolitical profanation in the work The pink notebook of Lori Lamby (1990), by Hilda Hilst. The principle that founded it concerns the fact that the current imperialist phase of capitalism, dominated by the USA, has as its dominant ideology the uninterrupted edition of a system of subjective confession whose power effect comes from the corporal configuration of the American style of being – that soft power. The study of the novel, whose plot is based on the confessions of the narrator-character (child), was structured around the perjury of the dominant biopolitical confession architecture after the Second World War. Therefore, to develop this dissertation, the interdisciplinary method was important to articulate the categories of biopolitics, in the perspective of Michel Foucault; of perjury and profanity, by Giorgio Agamben; of a state of exception, by Walter Benjamin; as well as literary theory and criticism.